(untitled) (Research, Society and Development, 2022)
Incluir o resumo em inglês. Maltodextrins are products of the partial hydrolysis of starch. They are classified according to the degree of hydrolysis of the starch and have various functional properties such as sweetness, solubility and viscosity. The variation in the final density of the product may not meet the specification of consumer companies. The product will not be properly positioned on the pallets or there will be damage to the packaging, due to inadequate storage, generating financial losses or product returns. The decision to evaluate maltodextrin quality control has matured after the realization that final density has an impact on storage and customer service. This work aims to verify the influence of the spray dryer drying parameters on the apparent density of maltodextrin, using data from available processes and the glass transition temperature under the operating conditions of the spray dryer. The study showed that among the quantified parameters, the vacuum applied in the spray dryer influenced the apparent density of maltodextrin and the dryer must operate with an average vacuum of 44 mmCa, since the other drying parameters presented similar values and, therefore, without influencing the apparent density. The calculated glass transition temperature (Tg) value for this drying system is between 150.0°C to 150.8°C, the dryer chamber outlet temperature between 106.12°C to 107.00°C and at air inlet temperature in the dryer between 192.08°C to 196.43°C. The dryer’s internal operating temperature is below the glass transition temperature of the product. This makes it possible to classify the product as vitreous.